2000
DOI: 10.1083/jcb.149.5.1053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intraorganellar Ca2+In Late Endosome–Lysosome Heterotypic Fusion and in the Reformation of Lysosomes from Hybrid Organelles

Abstract: We have investigated the requirement for Ca2+ in the fusion and content mixing of rat hepatocyte late endosomes and lysosomes in a cell-free system. Fusion to form hybrid organelles was inhibited by 1,2-bis(2-aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid (BAPTA), but not by EGTA, and this inhibition was reversed by adding additional Ca2+. Fusion was also inhibited by methyl ester of EGTA (EGTA-AM), a membrane permeable, hydrolyzable ester of EGTA, and pretreatment of organelles with EGTA-AM showed that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
356
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(374 citation statements)
references
References 59 publications
15
356
0
3
Order By: Relevance
“…Interestingly, in vitro homotypic fusion of yeast vacuoles requires a protein phosphatase I that is activated by calcium and calmodulin (40). Although a functional role has not yet been demonstrated for a protein phosphatase I in lysosomal fusion, there is a requirement for calcium and calmodulin in lysosomal fusion which mirrors the requirement for calcium and calmodulin in homotypic vacuolar fusion (41). Intriguingly, melanosomes are transported to the cell periphery in a manner that is dependent on myosin Va (42) and Rab27a (43).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in vitro homotypic fusion of yeast vacuoles requires a protein phosphatase I that is activated by calcium and calmodulin (40). Although a functional role has not yet been demonstrated for a protein phosphatase I in lysosomal fusion, there is a requirement for calcium and calmodulin in lysosomal fusion which mirrors the requirement for calcium and calmodulin in homotypic vacuolar fusion (41). Intriguingly, melanosomes are transported to the cell periphery in a manner that is dependent on myosin Va (42) and Rab27a (43).…”
Section: Discussionmentioning
confidence: 99%
“…Ion dysregulation could in turn have indirect consequences on other processes in OCA2-deficient cells. For example, alterations in intralumenal ion balance or pH can affect cellular membrane fusion events (Peters and Mayer, 1998;Ungermann et al, 1999;Pryor et al, 2000), perhaps explaining the accumulation of melanosomal cargo in vesicular structures in OCA2-deficient melanocytes (Manga et al, 2001). Moreover, disruption of OCA2 transport activity across the melanosomal membrane may indirectly alter ion concentrations or pH in the cytosol; for example, exogenous expression of OCA2 in Saccharomyces cerevisiae led to a depletion of cytoplasmic glutathione due to glutathione transport into the vacuole (Staleva et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another attractive hypothesis for impaired endolysosomal trafficking is a defect in vesicle fusion or ARTICLE fission processes. It has been postulated before that Ca 2 þ is required for vesicular fusion processes and thereby regulates trafficking of vesicular cargo proteins 30,32,33 . In accordance with this hypothesis, we found that in WT MEFs chelation of cytosolic Ca 2 þ by 1,2-bis(2-aminophenoxy)ethane-N,N,N 0 ,N 0 -tetraacetic acid tetrakis(acetoxymethyl ester) (BAPTA-AM) mimics the effect on EGF trafficking observed in TPC2 À / À MEFs (Fig.…”
Section: Articlementioning
confidence: 99%